PEMBINAAN IBADAH BAGI KARYAWAN RUMAH SAKIT MUHAMMADIYAH SELOGIRI SESUAI PUTUSAN TARJIH MUHAMMADIYAH PADA KEGIATAN BAITUL ARQAM - Andri Nirwana AN; Muthoifin; Kuswardani Dyah Ayu Kusumaningrum; Trisno Susilo; Haidar Edward Lumbantobing; Muhammad Thohir Ihsan (Universitas 'Aisyiyah Surakarta, 2025)
This community service program aims to improve the quality of worship of employees at Muhammadiyah Selogiri Hospital in accordance with the Muhammadiyah Tarjih Decisions Association. This activity was carried out in the form of Baitul Arqam activities held at the Pondok Sari 1 Hotel, Tawangmangu, Karanganyar, Central Java. This training focused on worship procedures such as prayer, fasting, zakat, as well as strengthening Muhammadiyah ideology so that employees are not only professional in their health care duties, but also become role models in religious practices in the workplace and community. The methods used included lectures, discussions, worship simulations, and self-reflection. This activity was attended by all ± 80 employees of Muhammadiyah Selogiri Hospital and guided by competent speakers in the field of Muhammadiyah tarjih. Evaluation was carried out through pre-tests and post-tests, observations of worship practices, and participant feedback as a basis for improving the development program in the future. The results of the community service program showed an increase in understanding and practice of correct worship according to tarjih, as well as the formation of a strong Islamic work culture in Muhammadiyah charitable efforts